From destination management towards governance of regional innovation systems: the case of South Tyrol, Italy - Pechlaner, Harald; Herntrei, M.; Pichler, S.; Volgger, M. (Emerald Group Publishing Limited, 2012)
In South Tyrol, Italy, and in other alpine destinations, the role of publicly financed tourism destination management has traditionally a strong focus on image promotion. In South Tyrol, three further regional public management organisations have recently been founded with the aim of developing the location by expanding its innovation and export capabilities, especially for small to medium-sized enterprises (SMEs). All four public organisations aim to increase the competitiveness of local companies through creating a more efficient management of destination and location. The cooperation between the four organisations and further public and private regional stakeholders might be regarded as a regional innovation system (RIS). This paper aims to analyse and discuss within the frame of a case study, the structure of the cooperation between the four public organisations and if it can be regarded as a developing South Tyrolean regional innovation system. The paper aims to focus on the roles of the four organisations, possible synergies and implications for regional governance.